Open-independent, open-locating-dominating sets - Suk J. Seo; Peter J. Slater (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2017)
A distinguishing set for a graph G = (V, E) is a dominating set D, each vertex v D being the location of some form of a locating device, from which one can detect and precisely identify any given